Atmospheric amines and ammonia measured with a chemical ionization mass spectrometer (CIMS) - Y. You; V. P. Kanawade; J. A. de Gouw; A. B. Guenther; S. Madronich; M. R. Sierra-Hernández; M. Lawler; J. N. Smith; S. Takahama; G. Ruggeri; A. Koss; K. Olson; et al. (Atmospheric Chemistry and Physics, 2014)
We report measurements of ambient amines and ammonia with a fast response chemical ionization mass spectrometer (CIMS) in a southeastern US forest and a moderately polluted midwestern site during the summer. At the forest site, mostly C3-amines (from pptv to tens of pptv) and ammonia (up to 2 ppbv) were detected, and they both showed temperature dependencies. Aerosol-phase amines measured thermal-desorption chemical ionization mass spectrometer (TDCIMS) showed a higher mass fraction in the evening with cooler temperatures and lower in the afternoon with warmer temperatures, a trend opposite to the gas-phase amines. Concentrations of aerosol-phase primary amines measured with Fourier transform infrared spectroscopy (FTIR) from micron and submicron particles were 2 orders of magnitude higher than the gas-phase amines. These results indicate that gas to particle conversion is one of the major processes that control the ambient amine concentrations at this forest site. Temperature dependencies of C3-amines and ammonia also imply reversible processes of evaporation of these nitrogen-containing compounds from soil surfaces in daytime and deposition to soil surfaces at nighttime. During the transported biomass burning plume events, various amines (C1–C6) appeared at the pptv level, indicating that biomass burning is a substantial source of amines in the southeastern US. At the moderately polluted Kent site, there were higher concentrations of C1- to C6-amines (pptv to tens of pptv) and ammonia (up to 6 ppbv). C1- to C3-amines and ammonia were well correlated with the ambient temperature. C4- to C6-amines showed frequent spikes during the nighttime, suggesting that they were emitted from local sources. These abundant amines and ammonia may in part explain the frequent new particle formation events reported from Kent. Higher amine concentrations measured at the polluted site than at the rural forested site highlight the importance of constraining anthropogenic emission sources of amines.